A METAPHOR TRANSLATION OF THE QUR’AN: A Comparative Analytical Study between Abdullah Yusuf Ali and Marmaduke Pickthall - Aizul Maula (IAIN Surakarta, 2016)
The metaphor is one of the main problems in translation because it covers the whole figurative language uses. It also includes the most figurative language used in the Qur’an. Different theories and approaches have been proposed with regard to metaphor translation. In this paper, I favor using a lexicological metaphor concepts that proposed by Dickin, where the dictionary becomes the main source of the analysis. This paper is analyzing and comparing the translation of metaphor in Qur’an and their corresponding translated English versions through the two selected translations. The data analyzed consists of ten examples representing two types of metaphor in this paper; both are lexicalized and nonlexicalized metaphor. The findings obtained from the analyses of the related data show that there are some techniques of metaphor translation of the Qu’ran, although every translator does not constantly translate metaphor with the same technique in the same type.